The keeping place - Carmody, Isobelle (New York : Random House, 2008)
After a Misfit is kidnapped, Elspeth is compelled to join the growing rebellion against the Council, but while her extraordinary mental powers could topple the corrupt authoritarian regime she is more concerned about destroying the remaining Beforetime weaponmachines.
Young Adult.
Young Adult
Keywords: Extrasensory perception -- Juvenile fiction; Human-animal communication -- Juvenile fiction; Kidnapping -- Juvenile fiction; Orphans -- Juvenile fiction; Persecution -- Juvenile fiction; Extrasensory perception -- Fiction; Human-animal communication -- Fiction; Kidnapping -- Fiction; Orphans -- Fiction; Persecution -- Fiction; Science fiction; Communication -- Fiction; Extrasensory perception -- Fiction; Kidnapping -- Fiction; Orphans -- Fiction; Persecution -- Fiction; Science fiction